Wawasan Nusantara dalam peraturan perundang-undangan Negara Republik Indonesia - Budiarto, M. (Ghalia Indonesia, 1980)
Commentary on government regulations and treaties relative to Indonesia's boundaries. Includes text of regulations and treaties.